Predictive factors of turnover intention of newly graduated nurses in their first year of employment: a longitudinal study - Jingjing Zhang; Lin Xia; Yuxin Wang; Ting Yi; Yan Wang; Enhong Zhou; Chaoqun Dong (BMC, 2024)
Abstract Background The turnover of newly graduated nurses is a severe challenge for healthcare systems, and so it is essential to identify its predictive factors. This study investigates whether professional commitment, career adaptability, career self-efficacy, anxiety, and depression levels before and after internship can predict the turnover intention of newly graduated nurses after one year of employment. Methods In a longitudinal study, 271 undergraduate nursing students recruited by convenience sampling were surveyed before internship (T1), after internship (T2), and after one year of employment (T3), with all surveys conducted on the Wenjuanxing survey platform ( www.wjx.cn ). Generalized linear models and restricted cubic spline models were used to explore possible linear and nonlinear relationships between turnover intention and the variables of interest. Results Professional commitment both pre-internship (β = −0.060, p = 0.007, 95% CI [− 0.104, − 0.016]) and post-internship (β = −0.053, p = 0.015, 95% CI [− 0.096, − 0.010]) can negatively predict turnover intention. There is also a negative linear relationship between post-internship career self-efficacy and turnover intention (β = −0.308, p < 0.001, 95% CI [− 0.436, − 0.180]). In addition, professional commitment both pre-internship (adjusted R 2 = 0.046, p = 0.004) and post-internship (adjusted R 2 = 0.068, p < 0.001), career self-efficacy both pre-internship (adjusted R 2 = 0.039, p = 0.008) and post-internship (adjusted R 2 = 0.116, p < 0.001), career adaptability both pre-internship (adjusted R 2 = 0.057, p < 0.001) and post-internship (adjusted R 2 = 0.039, p = 0.008), anxiety both pre-internship (adjusted R 2 = 0.035, p = 0.014) and post-internship (adjusted R 2 = 0.048, p = 0.003), and depression levels both pre-internship (adjusted R 2 = 0.031, P nonlinear = 0.021) and post-internship (adjusted R 2 = 0.053, p = 0.002) are nonlinearly associated with turnover intention. Conclusions Nursing educators and clinical care administrators must take action to enhance the professional commitment and career self-efficacy of nursing students during their internship. It is also important to pay attention to their career adaptability, as well as to any anxiety or depression that they may experience during clinical practice. This can help to reduce the turnover intention during the first year of their nursing career.